Simultaneous Mechanical and Topographical Characterization of Alginate Capsules - Virumbrales-Muñoz, María; Ochoa, Iñaki; Fernández, Luis (Jornada de Jóvenes Investigadores del I3A, 2017)
We used Atomic Force Microscopy (AFM) in order to characterize alginate microcapsules as for topography and stiffness simultaneously. Thus, we intend to identify those which are theoretically most biocompatible by this technique, reducing the need for animal testing.